Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Guru Yang Bersertifikasi Pendidik Pada Sekolah Menengah Kejuruan Negeri Kota Makassar - Suriany Sukardi; Purnamawati; Anas Arfandi (UNM Journal of Technology and Vocational, 2023)
This study aims to determine: (1) the effect of education level on the performance of educator certified teachers in Makassar City; (2) the influence of work motivation on the performance of educator-certified teachers in Makassar City; (3) the effect of teaching experience on the performance of educator-certified teachers in Makassar City (4) the effect of education level, work motivation and teaching experience on the performance of educator-certified teachers in Makassar City. The type of research used is descriptive quantitative. The sample in this study were 134 certified educator teachers in Makassar City. Data collection techniques using questionnaires and documentation. Data were analyzed using descriptive statistical analysis, analysis prerequisite test, and hypothesis testing. The research results show that; (1) there is an effect of education level on the performance of educator-certified teachers in Makassar City; (2) there is an effect of work motivation on the performance of educator-certified teachers in Makassar City; (3) there is an effect of teaching experience on the performance of educator-certified teachers in Makassar City (4) there is an influence of education level, work motivation and teaching experience on the performance of educator-certified teachers in Makassar City